Lipid Peroxidation And Respiratory Disorders To The Workers Pool (International Journal of Scientific Research and Management (IJSRM), 2015)
Chlorine gas is a chemical substance produced in the process of disinfection in swimming pool water. Exposure to chlorine causes changes in the body immunology mechanisms that generate oxidants or free radicals and some health complaints. The purpose of this study is analyzing the effect of exposure to chlorine on lipid oxidation measured in malondialdehyde levels (MDA) and respiratory disorders in workers pool in Surabaya. The method used in this research is analytic observational with cross sectional design. The population of this study is divided into disinfection operator and the administration on the three outdoor pools in Surabaya is selected based on several criteria. Large sample obtained by sampling randomly generated number of 24 people, each of 12 people on the carrier disinfection and administration. Data were analyzed using Mann Whitney test and regression test. Results of analysis illustrate that MDA levels significantly affected the concentration of chlorine in ambient air (p